Design and synthesis of a fluorinated quinazoline-based type-II Trk inhibitor as a scaffold for PET radiotracer development - Bernard-Gauthier, Vadim; Mahringer, Anne; Fricker, Gert (Bioorganic & medicinal chemistry letters, 2017)
NTRK1/2/3 fusions have recently been characterized as low incidence oncogenic alterations across various tumor histologies. Tyrosine kinase inhibitors (TKIs) of the tropomyosin receptor kinase family TrkA/B/C (encoded by NTRK1/2/3) are showing promises in the clinic for the treatment of cancer patients whose diseases harbor NTRK tumor drivers. We describe herein the development of [18F]QMICF ([18F]-(R)-9), a quinazoline-based type-II pan-Trk radiotracer with nanomolar potencies for TrkA/B/C (IC50=85-650nM) and relevant TrkA fusions including TrkA-TPM3 (IC50=162nM). Starting from a racemic FLT3 (fms like tyrosine kinase 3) inhibitor lead with off-target TrkA activity ((±)-6), we developed and synthesized the fluorinated derivative (R)-9 in three steps and 40% overall chemical yield. Compound (R)-9 displays a favorable selectivity profile on a diverse set of kinases including FLT3 (>37-fold selectivity for TrkB/C). The mesylate precursor 16 required for the radiosynthesis of [18F]QMICF was obtained in six steps and 36% overall yield. The results presented herein support the further exploration of [18F]QMICF for imaging of Trk fusions in vivo.